The Influence of Influencer Marketing, Content Marketing, and Online Advertising on Skincare Product Purchase Decisions on the Tiktok Application (Case Study on Palembang City Students) - Afriansyah, A.; Helmi, Sulaiman; Trisninawati, Trisninawati; Roni, Mukran (Asian Journal of Management Analytics, 2024)
This study aims to analyze the influence of Influencer Marketing, Content Marketing, and Online Advertising on the purchase decision of skincare products on the TikTok application, with a focus on students in the city of Palembang. Using quantitative methods and accidental sampling techniques from a population of 80 people, the data was collected through questionnaires and analyzed using SEM-Smart-PLS 3.0 for Windows. The findings of the study show that Influencer Marketing has a positive but insignificant effect, while Content Marketing and Online Advertising have a positive and significant influence on purchase decisions. Simultaneously, these three variables influenced the purchase decision with an R Square value of 0.841, indicating that 84.1% of the purchase decision variables could be explained by these three factors.